Functional ProTracer identifies patterns of cell proliferation in tissues and underlying regulatory mechanisms - Xiuxiu Liu; Maoying Han; Wendong Weng; Yan Li; Wenjuan Pu; Kuo Liu; Xufeng Li; Lingjuan He; Ruilin Sun; Ruling Shen; Yulong He; Dandan Liang; et al. (npj Regenerative Medicine, 2023)
Abstract A genetic system, ProTracer, has been recently developed to record cell proliferation in vivo. However, the ProTracer is initiated by an infrequently used recombinase Dre, which limits its broad application for functional studies employing floxed gene alleles. Here we generated Cre-activated functional ProTracer (fProTracer) mice, which enable simultaneous recording of cell proliferation and tissue-specific gene deletion, facilitating broad functional analysis of cell proliferation by any Cre driver.